Structural Requirements and Docking Analysis of Amidine-Based Sphingosine Kinase 1 Inhibitors Containing Oxadiazoles - Houck, Joseph D. (ACS Med Chem Lett, 2016)
[Image: see text] Sphingosine 1-phosphate (S1P) is a potent growth-signaling lipid that has been implicated in cancer progression, inflammation, sickle cell disease, and fibrosis. Two sphingosine kinases (SphK1 and 2) are the source of S1P; thus, inhibitors of the SphKs have potential as targeted cancer therapies and will help to clarify the roles of S1P and the SphKs in other hyperproliferative diseases. Recently, we reported a series of amidine-based inhibitors with high selectivity for SphK1 and potency in the nanomolar range. However, these inhibitors display a short half-life. With the goal of increasing metabolic stability and maintaining efficacy, we designed an analogous series of molecules containing oxadiazole moieties. Generation of a library of molecules resulted in the identification of the most selective inhibitor of SphK1 reported to date (705-fold selectivity over SphK2), and we found that potency and selectivity vary significantly depending on the particular oxadiazole isomer employed. The best inhibitors were subjected to in silico molecular dynamics docking analysis, which revealed key insights into the binding of amidine-based inhibitors by SphK1. Herein, the design, synthesis, biological evaluation, and docking analysis of these molecules are described.